A Review on Development of Solar Powered Multi Crop Cutter for Harvesting - T. N., Pathak; T. R., Vidhate; S. S., Jadhav; S. D., Thakur; A. P., Vadnere; V. E., Kothawade (International Journal For Research In Mechanical & Civil Engineering, 2017)
This paper represents the project work carried on development of solar power crop cutter. We have developed a compact mechanism for harvesting of crop cutter work on solar power so that we can an easy harvesting in minimum period of time. This set up is used to cut the multi-crops at a time, which help the small scale farmers. This cutter is been invented because of low cost, high compatibility, and use for rough use. This set up uses the solar power, which is provided with different blades, solar plate, rubber wheel, DC motor and battery arrangement which results in transmission of this solar power into rotary motion of cutter at the end of which the crops get cut easily and perform various task as per requirement. We have made changes in the existing machine to make its application easier at reduced cost. Our main aim in Cost and pollution control is attained through this Project work.